Improvement of camel milk-clotting: Usefulness of crude extract from green pods of carob (Ceratonia siliqua. L) as a substitute for commercial rennet: Improvement of camel milk coagulation - Omrani, Abir; Sboui, Amel; Mars, Wafa; Hamouda, Maha; Dbara, Mohamed; Hammadi, Mohamed; Khorchani, Touhami (Cellular and Molecular Biology, 2023)
Camel milk transformation into cheese remains an objective to be improved today. This study aimed to improve camel milk clotting using a crude extract from green pods of carob as a substitute for commercial rennet. The composition of the crude carob extract was determined for dry matter and protein content. Milk clotting conditions were studied at different temperatures, pH and CaCl2 concentrations. Milk clotting properties were assessed by milk clotting activity, specific activity and proteolytic activity. Enzymatic hydrolysis of camel milk caseins by crude carob extract and its inhibition were demonstrated by SDS-polyacrylamide gel electrophoresis. Crude carob extract analysis showed a protein and dry matter content of 23.26±0.5 mg/ml and 30.66±0.5 g/l, respectively. Optimal milk clotting activity was observed at 53.6 °C, pH 4.5, and 0.09 M CaCl2. The crude carob extract showed a high milk clotting activity (4.97 U/ml) and a low proteolytic activity (0.04U/ml) with camel milk. The cheese yield of curd produced from camel milk using crude carob extract was the highest (23.95%) compared with that of Camel chymosin (20.5%). The high ratio of milk-clotting to proteolytic activity shows the potential of this extract as a substitute for commercial rennet in the dairy industry.